2022
DOI: 10.3390/en15030962
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Efficiency of Energy and Carbon Emissions: A Review of Definitions, Models, and Input-Output Variables

Abstract: The importance and urgency of improving energy and carbon emissions efficiency in mitigating climate change and achieving carbon neutrality have become an increasingly relentless focus in recent years. Assessing the performance of energy saving and carbon emissions reduction is a significant necessity to achieve sustainable economic development. Therefore, from the perspective of production economics, this paper presents a review of the definition, models, and input-output variables for measuring total-factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 118 publications
0
2
0
Order By: Relevance
“…Likewise, the authors [17] propose the calculation of total factor energy efficiency (TFEE) using the concept of global production instead of domestic product, which excludes intermediate consumption. Another paper worthy to cite comes from the authors [18]. In that work, a literature review was carried out, and the authors found that the currently in use definitions of total-factor energy efficiency and total-factor carbon emissions efficiency are confusing and misleading.…”
Section: Energy Efficiency and Its Measurementmentioning
confidence: 99%
“…Likewise, the authors [17] propose the calculation of total factor energy efficiency (TFEE) using the concept of global production instead of domestic product, which excludes intermediate consumption. Another paper worthy to cite comes from the authors [18]. In that work, a literature review was carried out, and the authors found that the currently in use definitions of total-factor energy efficiency and total-factor carbon emissions efficiency are confusing and misleading.…”
Section: Energy Efficiency and Its Measurementmentioning
confidence: 99%
“…Based on the principle of simplicity, one of the widely applied expressions of carbon performance for Chinese enterprises with carbon emission is a ratio of sales and carbon emission, as used in [ 10 ]. Other approaches, such as input and output models with nonradial directional distance, are available to calculate the carbon performance [ 11 , 12 , 13 ]. From the perspective of corporate management, carbon performance is well applied to investigate the impact of carbon emission and green innovation on the financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reasonable and accurate carbon measurement is an important technical support to measure carbon emissions but also to achieve the "double carbon" target data support. Electricity and heating as an important industry of carbon dioxide emissions [5][6].…”
Section: Introductionmentioning
confidence: 99%